2009
DOI: 10.13181/mji.v18i2.351
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygenated water in Diabetes Mellitus

Abstract: Tujuan Mendapatkan gambaran pengaruh air oksigen terhadap diabetes mellitus. Metode Penelitian ini menggunakan disain uji klinik acak tersamar ganda, dengan 108 subyek diabetes mellitus. Setiap kelompok dibagi secara acak menjadi 2 sub kelompok. Satu subkelompok diberikan air oksigen dan subkelompok lain diberikan bukan air oksigen dalam 2 tahap intervensi, 45 hari dan 90 hari. Variabel yang diukur adalah kadar gula darah dan malondialdehyde (MDA) dengan pengendalian enam faktor perancu : jenis kelamin, umur, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…DM subjects with normal nutritional states also had a greater tendency for malondialdehyde (MDA) reduction after consuming oxygenated water for 45 days. Most subjects felt healthier after consuming oxygenated water [7]. Based on these studies, we believe that oxygenated water might improve cellular metabolism.…”
Section: Introductionmentioning
confidence: 77%
“…DM subjects with normal nutritional states also had a greater tendency for malondialdehyde (MDA) reduction after consuming oxygenated water for 45 days. Most subjects felt healthier after consuming oxygenated water [7]. Based on these studies, we believe that oxygenated water might improve cellular metabolism.…”
Section: Introductionmentioning
confidence: 77%
“…After all, it is not just in chickens that the positive effects of oxygenated water have been reported. Handajani et al [58] found that drinking such a solution was beneficial for diabetes mellitus, although other reports are sceptical. For example, Gruber et al [59] said that although there were no long-term detrimental effects on the liver, blood or immune system in humans, the presence of radicals in the blood was increased, albeit transiently.…”
Section: Oxyhydrogenmentioning
confidence: 99%
“…Namun berdasarkan penelitian Speit et al (2002), konsumsi minuman beroksigen tidak menimbulkan efek genotoksik berdasarkan uji in vivo dan in vitro. Penelitian dilakukan oleh Handajani et al (2009) menunjukkan kadar MDA pada subjek diabetes mellitus dengan status gizi normal yang diberikan minuman beroksigen selama 45 hari cenderung menurun. Studi yang dilakukan oleh Gruber et al (2005) menunjukkan konsumsi air beroksigen dalam jangka panjang tidak membahayakan hati, sel darah, dan sistem imun.…”
Section: Pendahuluan1unclassified